The governance of Higher Education - 50 years after the 25th of April (Revista Lusófona de Educação, 2024)
Taking the last 50 years as a temporal reference, this article seeks to characterize, in different momentsof the development of Portuguese higher education, how political mandates promote and articulate governance and management models. From the analysis of the participatory governance and management model during the years of the April Revolution to the model conveyed by the current legal framework, based on the autonomy and performance of institutions, and on quality assessment, it is clear that a path has been followed resulting in the limitation and decrease in the representativeness of the constituencies of academia, the under-representation of faculties/schools/departments in central decision-making bodies, and the strengthening of managerial functions of rectors and directors of organic units. Losses of collegiality in favour of centralization of decision-making processes and the predominance of managerial logics over academic ones have brought about a wide reconfiguration of governance and managementof institutions with losses of democracy in their contexts that must be considered.Keywords: Higher education governance and management; autonomy of higher education institutions; politicalmandate